Inert Gas Fusion of An Irradiated Oxide Fuel to Determine Its Retained Fission Gas Compositions - Park, Soon-Dal; Yeon, Jei-Won; Ha, Yeong-Keong; Song, Kyuseok (Asian Journal of Chemistry, 2012)
A clean and simple dissolution procedure involving an inert gas fusion without using mineral acids was developed in order to completely fuse an irradiated oxide fuel as an alloy form and thus quantitatively extract its retained gases. A commercial gaseous element analyzer for metals and alloys equipped with a small but powerful impulse furnace was employed for the fusion experiments. After fusion of an irradiated oxide fuel, the melt was analyzed using a special electron probe micro analyzer (EPMA), high-energy g-ray shielded, to evaluate the melting state. It was found that a 0.049 g fragment of an irradiated oxide fuel, ca. 55 GWd/tU, was clearly melted with 1 g of tin and 1 g of nickel at 850 A for 2 min under a helium atmosphere. The electron micro analysis revealed that the resultant melt under the fusion conditions contained no oxygen and it was assumed to be a kind of an intermetallic alloy form, a mixture of U-Sn-Ni. Recovery test results through the gas flow paths of the fusion instrument, which was equipped with several reagent columns for gas purification, showed that 96-98 % of the krypton and xenon was recovered during a 2 min collection period after injection. No residual gas was retained in the melt after the first fusion of a fragment of an irradiated oxide fuel at the established fusion conditions. Less than 10 min is sufficient to complete the analysis of retained fission gases in a spent fuel sample, including their extraction and measurement.